Mixed alkali effect in the physical and optical properties of xK2O-(25-x)Na2O-12.5MgO-12.5BaO-50B2O3 glasses. Issue 3 (1st July 2016) - Srinivas, G.; Ramesh, B.; Siva Kumar, J.; Shareefuddin, Md.; Chary, M.N.; Sayanna, R.
Abstract: Borate glasses with the composition x K2 O-(25- x )Na2 O-12.5MgO-12.5BaO-50B2 O3 ( x = 0, 5, 10, 15, 20 and 25 mol%) were prepared by the melt-quenching technique and were characterized using X-ray diffraction at room temperature. From the optical absorption spectra, the direct forbidden, direct allowed, indirect allowed, and indirect forbidden energy gaps; Urbach energy; refractive index ( n ); dielectric constant ( ɛ ); reflection loss ( R ); molar refraction ( R m ); and molar polarizability ( α m ) values of all of the glass samples were evaluated. R m, α m and Λ th increase with the increase of the K2 O content. The values of R, ɛ and n increase up to x = 10 mol% and then decrease above x = 10 mol%, which may be due to the mixed alkali effect. The density and molar volume values show the opposite behaviour and vary nonlinearly with the K2 O content, which manifests the mixed alkali effect in the present glass system. The infrared (IR) spectra of the borate glasses reveal the existence of 3- and 4-coordinated boron atoms. The specific vibrations of the Na-O, K-O, Mg-O, and Ba-O bonds were observed in an IR study.